The Role of Independent Reading on Reading Comprehension in The Second Years Students of MTs As’adiyah Putra 1 Sengkang - Amiruddin; Bahri, Syamsul; Fajriyani, Mathla'ul; Hartawan, Muh (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The main goal of the study is to see if implementing Independent Reading can help students improve their English reading comprehension. The research used a quasi-experimental procedure with two sets of pre-test and post-test designs to achieve the research goal. The participants in this study were As'adiyah Putra 1 Sengkang second-year students. The students in the sample were from VII A, who were treated with Independent Reading, and VII B, who were treated in a traditional manner. The experimental group's post-test mean score was greater than the control group's 78.27, according to the findings of this study. The significance (2-tailed) in the post-test was 0.00<0.05, according to the findings of the data analysis. Based on the findings of the analysis, suggests that there was a significant difference in English reading comprehension between students in the experimental group who were taught using Independent Reading and students in the control group. As a result, it can be inferred that students' English reading comprehension can be improved by the usage of Independent Reading